PENGELOLAAN SISTEM INFORMASI DESA DI KABUPATEN KUANTAN SINGINGI - Dina Aulia; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The village information system program is a village empowerment program as stated in the regulations regent of kuantan singingi regency. This program is a set of data and information utilization process tools to find out how the management of the village. The problems that occur in the village are still not in accordance with the contents of the kuantan singingi number 57 of 2017. where there are still village that have not implemented a village information system program there are only 10 village that have website, the use of wifi is not in accordance with the contents of the regent regulation, not all village information system content is contained in the onion river village website. information system program in Kuantan Singingi Regency and the factor that inhibit it. The theory used is G.R Terry in Badrudin, Terry in Badrudin, namely there are four indicators that influence management: planning, organizing, implementing, controling. This study uses secondary qualitative research types obtained though observation, interviews and documentation. The results of this study indicate that: first, the management of the village information system program in kuantan singingi regency is not yet optimal because stell lack of socialization. Second, the factors that hampered the management program of the village information system program in kuantan singingi regency namely: human resources, budget, and facilities/infrastructure.                                                                                                                          Keywords: Management, Program